The Influence of Incentives, Motivation, Work Environment and Leadership Style on Tapper Performance Kalikempit Plantation PT. Perkebunan Nusantara - Santika Permana; Suwignyo Widagdo; Yuniorita Indah Handayani (International Journal of Economics, Commerce, and Management, 2025)
The performance of an organization or company is influenced greatly and even depends on the quality and competitive ability of its human resources. Various factors can affect employee performance including incentives, motivation, work environment, and leadership style in the company. The purpose of this study was to test and analyze the effect of incentives, motivation, work environment, leadership style on the performance of tappers of Kalikempit Kebun PTPN I Regional 5. This research uses a quantitative approach with explanatory research type. The population in this study was 103 tappers of Kebun Kalikempit PT Perkebunan Nusantara I Regional 5. The sampling method uses saturated samples, where all employees totaling 103 tappers were sampled in this study. The data in this study were obtained using a questionnaire. Data analysis techniques use multiple linear regression analysis with SPSS 25. The results showed that: 1). Partially incentives have a significant influence on the performance of tappers, 2). Partially motivation has a significant influence on the performance of tappers, 3). Partially, the work environment has a significant influence on the performance of tappers, 4). Partially leadership style has a significant influence on the performance of tappers and 5) simultaneously incentive variables, motivation, work environment, and leadership style have a significant influence on the performance of tappers Kalikempit PTPN I Regional 5.